Chemosensing of honeybee parasite, Varroa destructor: Transcriptomic analysis. Issue 1 (December 2017) - Eliash, Nurit; Singh, Nitin; Thangarajan, Starlin; Sela, Noa; Leshkowitz, Dena; Kamer, Yosi; Zaidman, Ilia; Rafaeli, Ada; Soroker, Victoria
Abstract Chemosensing is a primary sense in nature, however little is known about its mechanism in Chelicerata. As a model organism we used the miteVarroa destructor, a key parasite of honeybees. Here we describe a transcriptomic analysis of two physiological stages for the Varroa foreleg, the site of primary olfactory organ. The transcriptomic analysis revealed transcripts of chemosensory related genes belonging to several groups. These include Niemann-Pick disease protein, type C2 (NPC2), gustatory receptors (GRs), ionotropic receptors (IRs), sensory neuron membrane proteins (SNMPs) and odorant binding proteins (OBP). However, no insect odorant receptors (ORs) and odorant co-receptors (ORcos) were found. In addition, we identified a homolog of the most ancient IR co-receptor, IR25a, in Varroa as well as in other members of Acari. High expression of this transcript in the mite's forelegs, while not detectable in the other pairs of legs, suggests a function for this IR25a-like in Varroa chemosensing.